Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Pengelolaan Keuangan Mahasiswa - Risma Nurfadzilah; Krisnawati Setyaningrum Nugraheni (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of financial literacy and lifestyle on financial management among students of the S1 Management Study Program at STIEPARI. Using a quantitative method with a sample of 92 students selected through the Slovin formula, data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The results show that financial literacy has a positive and significant effect on financial management (β=0.544; p<0.001), while lifestyle also has a significant effect but with a smaller contribution (β=0.015; p=0.040). The model explains 26.3% of the variation in student financial management (R²=0.263). These findings confirm the importance of improving financial literacy and lifestyle management to enhance student financial management